Oral hygiene improvement: a pragmatic approach based upon risk and motivation levels - Sgan-Cohen Harold D (BMC, 2008)
Abstract Good oral hygiene has always been the cornerstone of public and private dental health promotion. However, this has often been based upon incorrect assumptions. The public is not always willing and does not always need to change its oral health behavior to the same extent as that expected by the dental profession. The present commentary emphasizes the need to modify oral hygiene instruction according to specific risk and motivation levels. Dentistry needs to be flexible in accepting new evidence-based modalities of oral health promotion. Dentists, dental hygienists and the entire health care team need to accept that the traditional methods of oral health education are not always effective.